Sociedade teosófica e sua trajetória no Recife (1920-1990). - Barza, Valdenio Simoes (2023)
In the present work is presented the theme of esotericism in the city of Recife, focusing on the Theosophical Society between the years 1920-1990, as some stores were installed in the city during these years, where there was great activity with the dissemination of the principles of Theosophy, with a focus to the activities at the Estrela do Norte store, as this was the last store to be installed and the only one that remains active. This work discourses about how the relationships between the stores and their followers helped society to accept the theme. The research intends to present how the ST holds and disseminates its meetings, lectures and festivities and how it carries out the social interaction of this group with the local society. For this writing studies on the History of Religions were consulted. Specially those developed by Adone Agnolin and Carlos André Moura, as well as studies on History of the Present Time, proposed by François Dosse, also seeking to dialogue with the historiography of Brazil through books that bring historical moments that happened during the chosen timeframe, such as those presented by Lilia Schwarcz and José Guilherme Magnani. Research with the Society's internal documentation was also conducted, such as the founding minutes, proposal for admission of new members, in addition to consultations with city newspapers and searches on social networks. As a result, the report presents a reading of the organizational structure of the Society and how the members interact with each other and how cultural exchanges take place over time. Finally, a digital booklet aimed at high school students will be presented, formed by the compiling the collected data, accompanied by images and interactivity with the target audience.